Disease burden of myasthenia gravis in relation to oral corticosteroid dose: an insurance claims database study in Japan - Samukawa, Makoto; Konno, Shingo; Uzawa, Akiyuki; Taki, Kentaro; Todaka, Hiroshi; Mishiro, Izumi; Quelen, Céline; Łukowicz, Zuzanna; Majewska, Renata; Ohashi, Yohei (Frontiers in Neurology, 2025)
IntroductionOral corticosteroids (OCS) are used for maintenance treatment of myasthenia gravis (MG). Prolonged use of higher-dose OCS may provoke serious adverse events. Therefore, Japanese clinical guidelines recommend an OCS dose target of ≤5 mg/day. This retrospective study aimed to compare the burden of MG between patients achieving this target and non-achievers.MethodsData were obtained from three Japanese healthcare databases (JMDC, NHI and LSEHS) between 2014 and 2021. Patients with MG starting immunotherapy were enrolled and data were collected over 2 years following start of immunotherapy. Exposure to OCS was determined from medication delivery records; achievers and non-achievers of the ≤5 mg/day target during follow-up were identified. Outcomes evaluated were confirmed incident diabetes, new osteoporotic fracture, and total and MG-related costs.ResultsOverall, 459 patients were analyzed. Of these, 94 patients (58.4%) in the JMDC population, 96 (64.0%) in the NHI population and 119 (80.4%) in the LSEHS population achieved the ≤5 mg/day target. Incident confirmed diabetes in the JMDC population and new osteoporotic fractures in the LSEHS population were less frequent in target achievers than in non-achievers (p = 0.01 and p < 0.05, respectively). In target achievers in the JMDC and LSEHS populations, total and MG-related costs were lower (both p ≤ 0.01) than in non-achievers.DiscussionOCS dose target non-achievers carry a higher burden than achievers. Broader implementation of effective treatment strategies is required to reduce long-term use of higher-dose OCS and the associated burden.